Six-month outcomes from living well with diabetes: A randomized trial of a telephone-delivered weight loss and physical activity intervention to improve glycemic control - Eakin, E.; Reeves, M.; Winkler, E.; Healy, Genevieve; Dunstan, D.; Owen, N.; Marshal, A.; Wilkie, K. (2013)
Background: Intensive lifestyle intervention trials in type 2 diabetes contribute evidence on what can be achieved under optimal conditions, but are less informative for translation in applied settings. Purpose: Living Well with Diabetes is a telephone-delivered weight loss intervention designed for real-world delivery. Methods: This study is a randomized controlled trial of telephone counseling (n = 151) versus usual care (n = 151); 6-month primary outcomes of weight, physical activity, HbA1c; secondary diet outcomes; analysis was by adjusted generalized linear models. Results: Relative to usual care, telephone counseling participants had small but significantly better weight loss [-1.12 % of initial body weight; 95 % confidence interval (CI) -1.92, -0.33 %]; physical activity [relative rate (RR) = 1.30; 95 % CI, 1.08, 1.57]; energy intake reduction (-0.63 MJ/day; 95 % CI, -1.01, -0.25); and diet quality (3.72 points; 95 % CI, 1.77, 5.68), with no intervention effect for HbA1c (RR = 0.99; 95 % CI, 0.96, 1.01). Conclusions: Results are discussed in light of challenges to intervention delivery. © 2013 The Society of Behavioral Medicine.